The influence of early-life residential exposure to different vegetation types and paved surfaces on early childhood development: A population-based birth cohort study. (May 2022) - Jarvis, Ingrid; Sbihi, Hind; Davis, Zoë; Brauer, Michael; Czekajlo, Agatha; Davies, Hugh W.; Gergel, Sarah E.; Guhn, Martin; Jerrett, Michael; Koehoorn, Mieke; Nesbitt, Lorien; Oberlander, Tim F.; et al.
Highlights: Vegetated land cover exposure was positively associated with childhood development. Positive associations were stronger for tree cover relative to grass cover. Exposure to paved land cover was negatively associated with childhood development. Abstract: Background: Growing evidence suggests that exposure to green space is associated with improved childhood health and development, but the influence of different green space types remains relatively unexplored. In the present study, we investigated the association between early-life residential exposure to vegetation and early childhood development and evaluated whether associations differed according to land cover types, including paved land. Methods: Early childhood development was assessed via kindergarten teacher-ratings on the Early Development Instrument (EDI) in a large population-based birth cohort (n = 27, 539) in Metro Vancouver, Canada. The residential surrounding environment was characterized using a high spatial resolution land cover map that was linked to children by six-digit residential postal codes. Early-life residential exposure (from birth to time of EDI assessment, mean age = 5.6 years) was calculated as the mean of annual percentage values of different land cover classes (i.e., total vegetation, tree cover, grass cover, paved surfaces) within a 250 m buffer zone of postal code centroids. Multilevel models were used to analyze associations between respective land cover classes and early childhood development. Results: In adjusted models, one interquartile range increase in total vegetation percentage was associated with a 0.33 increase in total EDI score (95% CI: 0.21, 0.45). Similar positive associations were observed for tree cover (β-coefficient: 0.26, 95% CI: 0.15, 0.37) and grass cover (β-coefficient: 0.12, 95% CI: 0.02, 0.22), while negative associations were observed for paved surfaces (β-coefficient: −0.35, 95% CI: −0.47, −0.23). Conclusions: Our findings indicate that increased early-life residential exposure to vegetation is positively associated with early childhood developmental outcomes, and that associations may be stronger for residential exposure to tree cover relative to grass cover. Our results further indicate that childhood development may be negatively associated with residential exposure to paved surfaces. These findings can inform urban planning to support early childhood developmental health.